Komunikasi Interpesonal Orang Tua dan Anak dalam Meningkatkan Motivasi Belajar Membaca Al- Qur’an di Desa Datara Kabupaten Gowa - maem; Rahman, Ulfiani; Muzakkir (CV Kalimasada Group, 2024)
Abstract : This research aims to find out how the form of interpersonal communication of parents of child funds in increasing motivation to learn to read the Qur'an, to find out the inhibiting factors, and the implications of interpersonal communication of parents of child funds in increasing motivation to learn to read the Qur'an in Datara Village, Gowa Regency. This study uses a type of qualitative research with a descriptive phenomenological approach.The data sources in this study are primary and secondary data. The data collection methods used in this study are observation, interview, and documentation methods. Data processing and data analysis techniques use data collection techniques, data reduction, data presentation, and conclusion drawn.The results of the study show that the interpersonal communication between parents and children in increasing the motivation to learn to read the Qur'an in Datara Village, Gowa Regency is still said to be poor, because of the lack of parental empathy for children which results in children not being open and embarrassed to say the difficulties faced in the process of learning to read the Qur'an.Factors that hinder communication between parents and children are internal and external factors. Internal factors are the busyness of people, and external factors are the use of gadgets. The impact of the busy parents in Datara Village, Gowa Regency is that children tend to be closed and even feel embarrassed to tell about the difficulties they face, in the sense that children's openness to parents does not go as it should. Keywords: Interpersonal Communication, Motivation for learning the Qur'an